PENGARUH SISTEM INFORMASI AKUNTANSI DAN MOTIVASI TERHADAP KINERJA INDIVIDU (STUDI KASUS PADA PT. DHL SUPPLY CHAIN INDONESIA) - Sidauruk, Tagor Darius; Endang Widuri (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
The purpose of research is to know influence information accounting system and motivation to individual performance. The sample in this research includes 90 respondences worked at central office PT.DHL Supply Chain Indonesia. The sampling method is probability sampling. The collected of data used primary data and with reading information accounting system books. Test of data quality in this research are validity and reliability. Hypotesis test used multiple linier regression. The result in this research are information accounting system and motivation have significant influance to individual performance.